Pengelolaan Budaya Madrasah dalam Membentuk Siswa yang Berkarakter di MAS Amaliyah Sunggal - Intan Puspita Dewi; Kamil Kamil (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2023)
The purpose of this study is to find out how the management of madrasa culture in shaping students with character at MAS Amaliyah Sunggal. Forming the character of students in the madrasa environment can be through the culture of the madrasa, because through the culture of the madrasa which is applied together, character can be formed through exemplary and good examples. The management of madrasa culture at MAS Amaliyah Sunggal has an impact on the formation of student character. This is due to the management of the madrasa culture that has been prepared by the madrasa manager in order to form students with character. This research uses a qualitative research type with a descriptive method where the data collected is in the form of words, pictures, and numbers, even if the data in the form of numbers is only supporting data obtained through interviews, field notes, photos and personal documents or various other data.